Analysis of the degree of morphological-functional indices connection in throwing among athletes - Kuznetsova, Z. M.; Kuznetsov, S. A.; Ovchinnikov, Yu. D.; Golovko, P. V. (The Russian Journal of Physical Education and Sport, 2018)
A purposeful long-term training and upbringing of high class sportsmen is a difficult process, the quality of which depends on several factors. One of these factors is gifted children and teen-agers selection. The objectives of sports selection in throwing at the stage of initial training were indirectly solved in some scientific research works. This problem is still very urgent and still has its scientific and practical importance at a modern stage of sport development. The effectiveness of managing a sports training mainly depends on objective character and accuracy of information, which a trainer has about a sportsman during the trainings. Quantitative and qualitative indices registration of physical, technical and other kinds of training in athletic throwing will help to predict sports results of sportsmen-beginners. Materials. In the article the authors analyze the degree of morphofunctional indices connection with sports achievements in throwing among young men. Research methods: scientific literature analysis and summarizing, morphological peculiarities of athletes` analysis, testing, methods of mathematical statistics. Results. For sportsmen, who specialize in throwing, it is typical to have morphofunctional features of physical development. At the first stage of training longitudinal body sizes (upper and lower extremities and their segments), become very important especially for discus throwers (30,76+0,46 cm and 45,16+0,62 cm) and shot putters (32,78+0,51cm), and their ratio. Discus throwers and shot putters have longer upper extremities. This advantage is observed owing to all parts of the upper extremity - a shoulder and forearm with a hand. High class athletes` morphological peculiarities analysis revealed a high connection between the indices of body constitution, weight, height, weight-height index, extremities length and their segments and sports specialization and sportsmen`s effectiveness. Conclusion. For athletes who specialize in throwing, it is typical to have morphofunctional features of physical development. At the first stage of training longitudinal body sizes (upper and lower extremities and their segments), become very important especially for discus throwers (30,76+0,46 cm and 45,16+0,62 cm) and shot putters (32,78+0,51cm), and their ratio. Discus throwers and shot putters have longer upper extremities. This advantage is observed owing to all parts of the upper extremity - a shoulder and forearm with a hand.